Sandwich-Structured Graphene-Fe3O4@Carbon Nanocomposites for High-Performance Lithium-Ion Batteries - Zhao, Li; Gao, Miaomiao; Yue, Wenbo; Jiang, Yang; Wang, Yuan; Ren, Yu; Hu, Fengqin (ACS applied materials & interfaces, 2015)
Advanced anode materials for high power and high energy lithium-ion batteries have attracted great interest due to the increasing demand for energy conversion and storage devices. Metal oxides (e.g., Fe3O4) usually possess high theoretical capacities, but poor electrochemical performances owing to their severe volume change and poor electronic conductivity during cycles. In this work, we develop a self-assembly approach for the synthesis of sandwich-structured graphene-Fe3O4@carbon composite, in which Fe3O4 nanoparticles with carbon layers are immobilized between the layers of graphene nanosheets. Compared to Fe3O4@carbon and bulk Fe3O4, graphene-Fe3O4@carbon composite shows superior electrochemical performance, including higher reversible capacity, better cycle and rate performances, which may be attributed to the sandwich structure of the composite, the nanosized Fe3O4, and the carbon layers on the surface of Fe3O4. Moreover, compared to the reported graphene-Fe3O4 composite, the particle size of Fe3O4 is controllable and the content of Fe3O4 in this composite can be arbitrarily adjusted for optimal performance. This novel synthesis strategy may be employed in other sandwich-structured nanocomposites design for high-performance lithium-ion batteries and other electrochemical devices.